BUILDING USE RIGHTS OVER LAND MANAGEMENT RIGHTS IN SHOPPING CENTERS - Sidiq, Azhar (Pusat Unggulan Ipteks-PUI Universitas Jambi, 2023)
This article discusses arranging building use rights (HGB) over management rights (HPL). Management rights are rights to control land that the state directly controls. Which authorizes the right holders to plan the designation and use of the land in question, use the land to carry out their duties, hand over parts of the land to third parties with use rights for 6 (six) years, and receive annual income and or obligatory money. This research uses an empirical juridical method with the Wiltop Trade Center (WTC) Mall case approach that occurred in the Jambi Province area. In the discussion, it was found that the WTC management adhered to Article 2 of the Minister of Agrarian Regulation No. 9 of 1965 concerning the Implementation of the Conversion of Tenure Rights over State Land and Provisions Concerning Policy Further.Â It stipulates the conversion of tenure rights over State land into Management Rights, namely